(untitled) (Contemporary Journal of Social Science Review, 2025)
The paper discusses how lexemes that are not translated from Dari and Pashto into English in The Kite Runner by Khaled Hosseini (2003) can be seen as the means of maintaining the Afghan culture and influencing the experience of the reader. Although a lot of research has been carried out on the theme of trauma, exile and redemption, there is little emphasis on the micro-linguistic strategies in the text. Based on Lawrence Venuti framework of domestication and foreignization, this paper recognizes and classifies untranslated lexemes of kinship, religion, social hierarchy, and cultural object. The analysis indicates that Hosseini often does not translate words, especially in culturally meaningful areas, which can be a part of world-building and making the readers the cultural visitors and not the one who have completely adopted the culture. Although these results are tentative and confined to a few types of lexemes, they offer the perspective of the intersection of language and identity in the works of diasporic literature and highlight the potential of linguistic methods for students’ research.